2007
DOI: 10.1590/s1516-35982007000500017
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos metodológicos do comportamento ingestivo de ovinos alimentados com capim-elefante amonizado e subprodutos agroindustriais

Abstract: Um experimento foi realizado com o objetivo de definir o intervalo de tempo de registro do comportamento de ovinos Santa Inês. Utilizaram-se 18 ovinos machos, não-castrados, com peso corporal médio inicial de 22,62 kg. Os animais foram alojados em baias individuais e distribuídos ao acaso em seis tratamentos, constituídos de dois volumosos (capim-elefante amonizado ou não com 5% de uréia) e três concentrados (com 0% de farelo de cacau ou torta de dendê; com 40% de farelo de cacau; ou com 40% de torta de dendê … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
9
0
2
Order By: Relevance
“…Other results presented in literature, as those observed by Silva et al (2004) and Carvalho et al (2007), who tested intervals up to 30 min for eating behavior study of heifers and sheep, respectively, also indicated a 5-min interval as the most appropriate to obtain the estimations of behavioral activities. Like in the present study, the observation loss due to using intervals larger than 5 minutes in these studies also implied on inferior number of eating, rumination and idle periods, consequently resulting in longer time spent per period of these activities.…”
Section: Resultssupporting
confidence: 58%
“…Other results presented in literature, as those observed by Silva et al (2004) and Carvalho et al (2007), who tested intervals up to 30 min for eating behavior study of heifers and sheep, respectively, also indicated a 5-min interval as the most appropriate to obtain the estimations of behavioral activities. Like in the present study, the observation loss due to using intervals larger than 5 minutes in these studies also implied on inferior number of eating, rumination and idle periods, consequently resulting in longer time spent per period of these activities.…”
Section: Resultssupporting
confidence: 58%
“…Carvalho et al (2007b) observaram que a escala de cinco minutos é a mais recomendada por permitir detectar, detalhadamente, a distribuição do pastejo ao longo do dia.…”
Section: Resultsunclassified
“…Two days before the end of the performance trial, the time spent feeding, ruminating, and on other activities (idleness, drinking, defecation, and urination) was recorded during 24 h straight, in five-minute intervals, according to Carvalho et al (2007). During the night time observation, the environment was maintained under artificial illumination.…”
Section: Chemical Composition and In Vitro Digestibilitymentioning
confidence: 99%